Pengaruh Penambahan Urine dan Penghalusan Kohe Kambing terhadap Kualitas Pupuk Kompos Limbah Kulit Kopi Robusta (Coffea Canephora) - Rimbanu, Yosavat; Suharyatun, Siti; Tusi, Ahmad; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2025)
Goat manure and urine are potential additives to organic compost to improve compost quality due to their high nutrient content, particularly nitrogen, phosphorus, and potassium (NPK). This study aimed to analyze the effects of manure grinding and the addition of goat urine on the quality of compost produced from robusta coffee husk waste (Coffea canephora). The experiment was conducted using a Completely Randomized Design (CRD) with four treatments: A1 (coffee husk + unground goat manure), A2 (coffee husk + unground goat manure + goat urine), A3 (coffee husk + ground goat manure), and A4 (coffee husk + ground goat manure + goat urine). Each treatment was replicated three times. The observed parameters included moisture content, temperature, pH, particle density, nutrient content (N, P, K, C/N ratio), and compost color. The results indicated that treatment A4 produced the best compost quality, with moisture content of 59–60%, temperature ranging from 27 to 29°C, pH 6.8–7.2, and nutrient contents of N 2.43%, P 0.78%, K 1.62%, and a C/N ratio of 17.03. The color change from light brown to dark brown–black indicated compost maturity. Increased particle density reflected a more compact and stable compost structure. The combination of material grinding and the addition of goat urine proved to accelerate the decomposition process and improve both the physical and chemical quality of the resulting compost.